Laccases and Peroxidases Co-Localize in Lignified Secondary Cell Walls throughout Stem Development - Hoffmann, Natalie; Benske, Anika; Betz, Heather; Schuetz, Mathias; Samuels, A. Lacey (Plant physiology (Bethesda), 2020)
Lignin, a critical phenolic polymer in secondary cell walls of plant cells, enables strength in fibers and water transportation in xylem vessel elements. Secreted enzymes, namely laccases (LACs) and peroxidases (PRXs), facilitate lignin polymerization by oxidizing lignin monomers (monolignols). Previous work in Arabidopsis ( ) demonstrated that AtLAC4 and AtPRX64 localized to discrete lignified cell wall domains in fibers, although the spatial distributions of other enzymes in these large gene families are unknown. Here, we show that characteristic sets of putative lignin-associated LACs and PRXs localize to precise regions during stem development, with LACs and PRXs co-occurring in cell wall domains. AtLAC4, AtLAC17, and AtPRX72 localized to the thick secondary cell wall of xylem vessel elements and fibers, whereas AtLAC4, AtPRX64, and AtPRX71 localized to fiber cell corners. Interestingly, AtLAC4 had a transient cell corner localization early in fiber development that disappeared in the mature stem. In contrast with these secondary cell wall localizations, AtLAC10, AtPRX42, AtPRX52, and AtPRX71 were found in nonlignified tissues. Despite ubiquitous PRX occurrence in cell walls, PRX oxidative activity was restricted to lignifying regions during development, which suggested regulated production of apoplastic hydrogen peroxide. Relative amounts of apoplastic reactive oxygen species differed between lignified cell types, which could modulate PRX activity. Together, these results indicate that precise localization of oxidative enzymes and differential distribution of oxidative substrates, such as hydrogen peroxide, provide mechanisms to control spatiotemporal deposition of lignin during development.